2019
DOI: 10.26905/jkdp.v23i1.2084
|View full text |Cite
|
Sign up to set email alerts
|

The effect of commodity price changes and USD/IDR exchange rate on Indonesian mining companies’ stock return

Abstract: There are many variables which will be influencing stock return. Some of those variables are come from the commodity market, such as gold, price and crude oil price changes, and also come from the exchange rate market. This study is about to test the effect of changes prices of gold, silver, crude oil, and exchange rate to the stock return of mining sector companies in Indonesia. There are 48 companies engaged in the mining sector listed on the Indonesia Stock Exchange (IDX). From 48 companies this study uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…The fluctuations or movements in the stock prices can occur due to many factors, such as commodity prices. Arfaoui and Ben Rejeb (2017) found that the world oil price movement has a significant effect on the stock price, this finding also supported by Hersugondo, Robiyanto, Wahyudi, and Muharam (2015); Robiyanto (2018), while Putra and Robiyanto (2019) found that the precious metal prices can affect the mining stock price. This could happen because these commodities prices can affect the profitability level.…”
Section: Introductionsupporting
confidence: 56%
“…The fluctuations or movements in the stock prices can occur due to many factors, such as commodity prices. Arfaoui and Ben Rejeb (2017) found that the world oil price movement has a significant effect on the stock price, this finding also supported by Hersugondo, Robiyanto, Wahyudi, and Muharam (2015); Robiyanto (2018), while Putra and Robiyanto (2019) found that the precious metal prices can affect the mining stock price. This could happen because these commodities prices can affect the profitability level.…”
Section: Introductionsupporting
confidence: 56%
“…The fluctuations or movements in the stock prices can occur due to many factors, such as commodity prices. Arfaoui and Ben Rejeb (2017) found that the world oil price movement has a significant effect on the stock price, this finding also supported by Hersugondo, Robiyanto, Wahyudi, and Muharam (2015); Robiyanto (2018), while Putra and Robiyanto (2019) found that the precious metal prices can affect the mining stock price. This could happen because these commodities prices can affect the profitability level.…”
Section: Introductionsupporting
confidence: 53%
“…In this study, the researcher will analyze the data and prove the existing hypothesis by explaining the relation of the independent variable towards the dependent variable or what so-called as associative research (Putra and Robiyanto, 2019). As discussed earlier in the previous chapter, this study intends to know the relation of exchange rate and gold price towards Jakarta Composite Index volatility.…”
Section: Datamentioning
confidence: 99%
“…Thus, due to the ARCH model"s shortcoming, Generalized Auto-Regressive Conditional Heteroscedasticity (GARCH) model was advanced by Bollerslev (1986) in order to catch more long lagged effects with less parameters and the conditional variance. Moreover, GARCH model can be used for a research which has data abnormalities and heteroscedasticity issue (Putra & Robiyanto, 2019).…”
Section: Technique Of Analysismentioning
confidence: 99%